Chemical constituents of root and stem bark of Erythrina brucei. (June 2018) - Gurmessa, Getahun Tadesse; Kusari, Souvik; Laatsch, Hartmut; Bojase, Gomotsang; Tatolo, Godiraone; Masesane, Ishmael B.; Spiteller, Michael; Majinda, Runner R.T.
Graphical abstract: Highlights: Two new isoflavanones, erybrucein A and B, were isolated from Erythrina brucei . Nineteen known compounds isolated in parallel, several for first time in this plant. Structures established by extensive spectroscopic and spectrometric analyses. Antibacterial and antioxidant activities of the compounds evaluated. Abstract: Two new isoflavanones, erybrucein A and B (1, 2 ), together with nineteen known compounds are reported herein from the stem and root bark of the Ethiopian medicinal plant, Erythrina brucei . All known compounds, except erythraline (19 ), have been isolated for the first time from E. brucei . Their structures were established on the basis of extensive spectroscopic and spectrometric analyses (1D and 2D NMR, CD, IR and ESI-HRMS n ) and confirmed by comparison with reported- and DFT-calculated data. The absolute configuration of kenusanone F (3 ) and the 7-methyl ether (4 ) were determined in the same way. Antibacterial properties as well as DPPH radical scavenging activities of the new isoflavanones and selected known compounds were evaluated. Although most tested compounds showed weak activity against the tested organisms, erybrucein B (2 ) showed moderate activity (MIC = 0.062 mg/mL) against Bacillus cereus . In the DPPH radical scavenging assays, compounds1, 2, and3 showed moderate activity whereas two other compounds showed high activity.